MUTU BROWNIES MENJADI PELUANG USAHA RUMAHAN - Tirta Mulyadi; Wijaya Adi Putra; Frangky Silitonga (JURNAL CAFETARIA, 2022)
Brownies have a solid brownish texture cake that gives the brownie its signature. Brownies made up of the first American pastry known in 1897. The brownie's own name is inspired by the color of a brownish cake. The brownie contains the basic ingredient of wheat flour. Wheat flour is made of flour or fine powder that comes from refined wheat kernels and is then generally used in the making of noodles, cakes, and bread. Wheat flour contains many starch, a complex carbohydrate that is not dissolved in water. Wheat flour also contains a protein in the form of gluten, which plays a role in determining food plasticity. This type of study is the study of an experiment that is made of brownies using two distinct brands of wheat flour to illustrate comparisons in terms of taste, aroma, texture, and color. Data collection techniques use instruments that include hedonic quality tests and hedonic tests with data analysis used in mann-whitney tests to determine the difference between the two treatments or treatment. The study instrument USES a questionnaire with a total of 15 trained panelists. Hedonic quality tests indicate differences in the flavor, aroma, texture, and color between the blue triangle and the wheat flour of sania. For hedonic panelis, test results like the flavor, aroma, and texture brownies that use blue triangles of flour instead of sania wheat.